Asymmetric [3+2] Cycloaddition of Olefins with Morita–Baylis–Hillman Carbonates Catalyzed by BINOL-Based Bifunctional Phosphine - Cui, Hai-Lei; Tang, Xue; Li, Meng-Fan; Xu, Xing-Jie; Shi, Yin (Synlett, 2019)
We have developed a series of novel BINOL-based phosphines. These bifunctional organocatalysts can be used in the [3+2] cycloaddition of electron-deficient olefins and Morita–Baylis–Hillman (MBH) carbonates. Moderate to excellent yields (up to >99%) and good to excellent enantioselectivities (up to 95% ee) can be obtained in the cycloaddition reaction of maleimides and MBH carbonates. The application of these novel phosphines can be further extended to the asymmetric synthesis of chiral spirooxindoles (up to 85% ee). The results in this study indicate that the BINOL moiety plays an important role in stereocontrol.
Keywords: BINOL; phosphine; organocatalyst; Morita–Baylis–Hillman derivative; cycloaddition